PENUGASAN BERBASIS MEDIA MIND MAP SEBAGAI INSTRUMEN PENILAIAN HASIL BELAJAR TENTANG KALOR DAN PERPINDAHANNYA - Sapitri, Dewi Wulan; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the using of mind maps as an instrument for evaluating the learning outcomes of VII grade students about heat concept and its displacement in SMP Negeri 1 Tumbang Titi. Classroom Action Research (CAR) is the type of this research. The subjects of this research were VII grade students of SMP Negeri 1 Tumbang Titi. 32 students of VII B as the samples. The data collected in this study are students' ability in making mind maps, student learning outcomes that evaluated by mind maps, and the implementation of learning assignments to make mind maps. The results showed that mind maps can be used as instruments for assessing student learning outcomes. Students? ability in making mind maps of the first cycle were 78% excellent category and 22% (enough categories), while the second cycle were 93% (good category) and 7% (enough categories). Students? learning outcomes in the first cycle were 78% complete and 22% were incomplete. 87.5% of students in the cycle II were complete and 12.5% were incomplete. The implementation of instructional learning makes mind maps of the first cycle of 81% and the second cycle of 100%. Based on the results of this study, mind map assignment are expected as an instrument for assessing student learning outcomes. Keywords: Assignments, Heat and Diplacement, Instrument Assessment, Mind Map